La organización en la universidad pública de Costa Rica: una propuesta - Ángel Ruiz-Zúñiga (Universidad Nacional, Costa Rica, 2004)
A wide international and national perspective of Higher Education is developed in order to sustain a proposal for the internal organization of public Universities in Costa Rica. Organizational axis and principles are established, and the concept of "areas" is proposed as the central structural level in academic life in order to improve public universities' operation. The approach presented here views public universities as being part of one integrated reality in which common objectives are shared.